2019
DOI: 10.1111/ajo.13098
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and workplace stress in Australian and New Zealand obstetrics and gynaecology trainees: A cross‐sectional survey

Abstract: Results: Two-hundred and thirty-one (36%) valid responses were received. The mean resilience score was moderate (mean = 77; SD = 11). Resilience was significantly associated with general health (F = 7.5, P = 0.007), depression in the last two weeks (F = 4.4, P = 0.013) and seriously considering leaving the program at some point (F = 15.4, P < 0.001). Most participants (204; 88%) stated improvements could be made to the level of trainee support; with over half identifying the support they received from RANZCOG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Undoubtedly, these factors are expected to result in significant burnout and subsequent adverse outcomes such as deterioration of health and training drop-out. [1][2][3] This is well reflected in a recent study by Ryder et al who reported alarmingly high prevalence of burnout, workplace stress and depression (55%, 62% and 45%, respectively) in Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) trainees. 1 Grit is synonymised as a unique human trait combining passion and perseverance and is believed to be a predictor for personal achievement and career success.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Undoubtedly, these factors are expected to result in significant burnout and subsequent adverse outcomes such as deterioration of health and training drop-out. [1][2][3] This is well reflected in a recent study by Ryder et al who reported alarmingly high prevalence of burnout, workplace stress and depression (55%, 62% and 45%, respectively) in Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) trainees. 1 Grit is synonymised as a unique human trait combining passion and perseverance and is believed to be a predictor for personal achievement and career success.…”
Section: Introductionmentioning
confidence: 75%
“…[1][2][3] This is well reflected in a recent study by Ryder et al who reported alarmingly high prevalence of burnout, workplace stress and depression (55%, 62% and 45%, respectively) in Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) trainees. 1 Grit is synonymised as a unique human trait combining passion and perseverance and is believed to be a predictor for personal achievement and career success. 4,5 Its association with the success of medical training has been repeatedly examined and reported in the literature.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…3 Specifically, self-reported burnout in Australian Obstetrics and Gynaecology trainees has a prevalence of 46-55%. [4][5] This prevalence has been attributed in part to the nature of obstetric care, which requires immediate attention to clinical emergencies, prolonged and complex surgical procedures, litigation threat and lengthy shifts. [6][7] Performance anxiety also plays a role, with junior doctors expressing fears regarding public criticism as a contributory factor.…”
Section: Introductionmentioning
confidence: 99%
“…A systemic review of 54 studies involving 17 560 individuals showed that the prevalence of depression or depressive symptoms among residents from a variety of specialities was between 20.9 and 43.2% with an increase in symptom prevalence over the course of the calendar year 3 . Specifically, self‐reported burnout in Australian Obstetrics and Gynaecology trainees has a prevalence of 46–55% 4–5 . This prevalence has been attributed in part to the nature of obstetric care, which requires immediate attention to clinical emergencies, prolonged and complex surgical procedures, litigation threat and lengthy shifts 6–7 .…”
Section: Introductionmentioning
confidence: 99%